MENINJAU KEMBALI PENGGUNAAN EMAS DAN PERAK SEBAGAI MATA UANG YANG LEBIH STABIL NILAINYA - Haryadi, Imam (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2013)
Money was the most significant invention n in the history of human civilization; it can make any kind of transaction easier in the sector that can be fulfilled by the direct exchange goods by goods. Nowadays, the existence of paper money as the legal tender of government has turning the money into a commodity and instrument of speculation that lead into many financial crisis because of the unstable value of it Specially; this paper deals with three main questions. First, how was the chronology of money's invention? Second, is there any better solution for the financial crisis that based on the using of paper money which has no intrinsic value? This is a literature research by historical approach and using deductive and inductive method with content analysis as the way to analyze the result By the research conclude that the main problem is the non-intrinsic value of money issued by the government and the usury in it has lead to the financial crisis again and again, than the government should issued the paper money that has to be pegged to both or one of the precious metal gold or silver as the formal standard to maintain its value